Dosimetry of cell-monolayers in multiwell plat - Freudenberg, R.; Andreeff, M.; Oehme, L.; Kotzerke, J. (Nuklearmedizin - NuclearMedicine, 2009)
Aim: Irradiation of cells in-vitro with unsealed radionuclides is often carried out in cylindrical multi-well-plates. For calculation of the absorbed dose using the sphere model is common. This model assumes a spherical distribution of activity. However, by physical aspects a dose reduction in the peripheral area of the activity volume is expected and predicted especially for high-energy beta-emitting radionuclides. The impact on cellular dosimetry shall be depicted in this paper. Methods: The dose-distribution inside a multi-well-plate was calculated by convolving the dose distribution around a point source with a given activity. This was performed for the radionuclides I-131, Re-188 and Y-90 in wells of different sizes. For comparison the sphere dose was also calculated. Results: Depending on the beta-energy differences up to 40% between the mean calculated dose and the mean sphere dose were found, whereby calculated dose was always lower than the sphere model prediction. Furthermore a fall-off was calculated for the bottom-dose compared to dose in the centre. An analytical expression was revealed for the bottom-dose with respect to the filling level for three different wells. Conclusion: The shape of geometry and the influence on dose distribution must be considered especially at in-vitro exposure with low energy and short range beta-emitting radionuclides. There could be a great impact for exact dose estimation, which is especially necessary to know for comparison of different irradiation experiments (e.g. different radionuclides, various irradiation geometries or comparison with x-rays).
Keywords: In-vitro dosimetry; sphere model; dose-pointkernels